Dysembryoplastic neuroepithelial tumor: A rare brain tumor not to be misdiagnosed - Sukheeja, Deepti; Mehta, Jayanti (Asian Journal of Neurosurgery, 2016)
Dysembryoplastic neuroepithelial tumor (DNET) is a recently described, morphologically unique, and surgically curable low-grade brain tumor which is included in the latest WHO classification as neuronal and mixed neuronal-glial tumor. It is usually seen in children and young adults. The importance of this particular entity is that it is a surgically curable neuroepithelial neoplasm. When recognized, the need for adjuvant radiotherapy and chemotherapy is obviated. We hereby present a case report of an 8-year-old male child who presented with intractable seizures and parieto-occipital space occupying lesion. Histologically, the tumor exhibited features of WHO grade I dysembryoplastic neuroepithelial tumor which was further confirmed by immunohistochemistry.
Keywords: Child; dysembryoplastic neuroepithelial tumor; histopathology